Antioxidant and spermatozoa: a complex story- A review - SARASWAT, SONIA; JINDAL, S K; KHARCHE, S D (The Indian Journal of Animal Sciences, 2016)
The artificial insemination is a common practice in domestic animals, but the use of frozen semen compromises the fertility of goat spermatozoa based on pregnancy rates from AI. This could be due to a poor resistance of goat spermatozoa to cryopreservation stresses compared to sperm from other domesticated mammals. Lipid peroxidation caused by reactive oxygen species limits the success in this species. Reports revealed that inclusion of antioxidants in cryopreservation media improved quality of semen against LPO. Moreover, inclusion of enzymatic and nonenzymatic antioxidants (vitamin C, glutathione reduced etc) in diluents at appropriate concentration can help in holding the semen at refrigeration temperature for many days.